Vasodilatation stress cardiovascular magnetic resonance: feasibility and safety in a monocentric prospective study. (8th February 2021) - Pezel, T; Garot, P; Hovasse, T; Toupin, S; Unterseeh, T; Morice, MC; Champagne, S; Louvard, Y; Sanguineti, F; Garot, J
Abstract: Funding Acknowledgements: Type of funding sources: None. BACKGROUND: Cardiovascular magnetic resonance imaging (CMR) has emerged as an accurate technique that can assess ventricular function, stress myocardial perfusion, and viability, without radiation. Recent studies have shown that stress CMR would be the best test to predict obstructive coronary artery disease (CAD) with a good safety. PURPOSE: The aim of our study was to assess the feasibility and incidence of immediate complications of stress CMR in a tertiary Cardiovascular Center with CMR Laboratory dedicated. METHODS: Prospective registry of vasodilator stress CMR in a French center with CMR expertise included all consecutive patients referred for vasodilator stress perfusion CMR to detect an obstructive CAD between 2008 and 2020. Stress CMR was performed at 1.5 T using dipyridamole. The clinical and demographic data, quality of test, CMR findings, haemodynamic data, and complications were prospectively recorded. RESULTS: Stress CMR was performed in 35, 157 patients (98.2% of requested). The study could not be performed due to claustrophobia in 0.3%. Quality was optimal in 93.1%, suboptimal in 6.4%, and poor in 0.5% of studies. Images were diagnostic in 97.9% of patients. No patient died or had acute myocardial infarction during the test. Moreover, 56 patients (0.16%) had severe immediate complications, and one anaphylactic shock post-gadolinium. The only factor significantly associated with higher incidence of serious complications was the detection of inducible ischaemia (p < 0.001). Incidence of non-severe complications was low (1.5%), severe controlled chest pain being the most frequent. Minor symptoms occurred frequently (35.5%). CONCLUSION: Performance of stress CMR is safe with very high image rate of satisfactory quality to perform the diagnosis in a referral population. Inducible ischaemia was the only factor identified which was associated with serious complications.